Maximum values of Ni2+, Cu2+, Pb2+ and Zn2+ in the biomonitor Tillandsia capillaris (Bromeliaceae): Relationship with cell membrane damage - Wannaz, Eduardo Daniel (2011)
Although several plants belonging to the Bromeliaceae family have been used as heavy metal accumulators in biomonitoring studies, their accumulation ability has not been investigated. The present study obtained the accumulation rates of Ni2+, Cu2+, Pb2+ and Zn2+ in leaves of Tillandsia capillaris and revealed their effects on lipid peroxidation by measuring the Malondialdehyde content (MDA). Leaves of T. capillaris were exposed to different metallic solutions of Cu2+, Ni2+, Pb2+ and Zn2+ cations. After this exposure period, the accumulation of these ions was measured by Total Reflection X-Ray Fluorescence (TXRF) analysis with Synchrotron Radiation, and the MDA content was calculated. Data sets were evaluated by a one-way analysis of variance (ANOVA) and a fitted regression hyperbola model. The results showed significant differences in the accumulation efficiencies of the cations under study. In addition, the enrichment factor (EF) estimated for these cations was higher for Ni2+, suggesting a greater affinity of the plant with this element. Over time, all the metals under study caused significant increases in the MDA content, indicating their toxicity effects even in the most diluted solutions used in this study.